Análisis de falla en modo mixto I y II bajo cargas cuasi-estáticas y dinámicas por impacto en un compuesto de reparación aeronáutica (2021)
Delamination fracture analysis of multi-layered composite materials poses a difficult structural problem due to its high complexity and combination of physical phenomena. Interest in predicting composite fracture was grown in the last years, due to their specific applications in the aerospace and aeronautic industries. Previous studies had shown that an accurate prediction failure needs to be accompanied by material testing in all mix-mode combinations which involve complex experimental setups. This study presents the experimental and numerical results for mode I, mode II and mixed-mode I+II, fracture toughness by utilizing the mixed-mode bending test of our main device. The material tested was a fiberglass/Epoxy composite manufactured by wet lay-up vacuum bagging, which is commonly used in aeronautic repair applications. Critical energy release rates were calculated for individual mode I and II and then utilized in conjunction with the experimental data to calibrate the Power law failure criteria. The effects of the mode of loading in the crack growth rate at the dynamic test are presented in this study.